Government Spending in Education and Economic Growth in Cameroon: A Vector Error Correction Model Approach - DOUANLA, Tayo Lionel; ABOMO, Fouda Marcel Olivier (Journal of Research in Educational Sciences; Vol 7 No 8 (2015): Journal of Research in Educational Sciences, 2015)
This study aims at assessing the effect of government spending in education on economic growth in Cameroon over the period 1980-2012 using a vector error correction model. The estimated results show that these expenditures had a significant and positive impact on economic growth both in short and long run. The estimated error correction model shows that an increase of 1% of the growth rate of private gross fixed capital formation and government education spending led to increases of 5.03% and 10.145 % respectively in the long-run on economic growth. Education spending thus appears as one of the main driving force of the economic growth process in Cameroon.